Pathological Role of Tonsillar B Cells in IgA Nephropathy - Yusuke Suzuki; Hitoshi Suzuki; Junichiro Nakata; Daisuke Sato; Tadahiro Kajiyama; Tomonari Watanabe; Yasuhiko Tomino (Clinical and Developmental Immunology)
Although impaired immune regulation along the mucosa-bone marrow axis has been postulated to play an important role, the pathogenesis of IgA nephropathy (IgAN) is unknown; thus, no disease-specific therapy for this disease exists. The therapeutic efficacy of tonsillectomy or tonsillectomy in combination with steroid pulse therapy for IgAN has been discussed. Although randomized control trials for these therapies are ongoing in Japan, the scientific rationale for these therapies remains obscure. It is now widely accepted that abnormally glycosylated IgA1 and its related immune complex (IC) are probably key molecules for the pathogenesis, and are thus considered possible noninvasive biomarkers for this disease. Emerging evidence indicates that B cells in mucosal infections, particularly in tonsillitis, may produce the nephritogenic IgA. In this paper, we briefly summarize characteristics of the nephritogenic IgA/IgA IC, responsible B cells, and underlying mechanisms. This clinical and experimental information may provide important clues for a therapeutic rationale.